Proposal of a System for Estimating the Assembly Time in Small and Medium-Sized Enterprises - Štefan Václav; Albert Mareš; Stanislaw Legutko*; Peter Košťál; Daynier Rolando Delgado Sobrino (Tehnički Vjesnik, 2020)
This paper presents the results of the development of a specialized modifiable system for estimating the assembly time in practice. The proposal is mainly intended for small and medium-sized enterprises, which require the application of sophisticated and cost-effective solutions given the arising competitiveness in the assembly sector. The ATES system, i.e., Assembly Time Estimation System, which was created in Excel, was tested in the LEANLAB laboratory. The results correspond with current trends in this area and suggest directions for further development, especially in the field of 3D CAD systems and virtual reality.